2009
DOI: 10.1007/s11999-008-0697-2
|View full text |Cite
|
Sign up to set email alerts
|

THA with Highly Cross-linked Polyethylene in Patients 50 Years or Younger

Abstract: Highly cross-linked polyethylene has been associated with low in vitro wear, but also has decreased in vitro ultimate yield strength. We therefore asked whether highly cross-linked polyethylene would result in lower outcome scores, wear, or early failure in a young patient population. Seventy THAs in 64 patients were performed using a highly cross-linked (electron beam-irradiated to 9 Mrads) acetabular liner and a cobalt-chrome femoral head. The average age of the patients at surgery was 41 years (range, 19-50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 45 publications
3
15
0
Order By: Relevance
“…Rajadhyaksha et al, also comparing Crossfire with a control group of N 2 Vac polyethylene, noted a difference in lysis similar to ours (0% versus 14.8%) [23]. Some studies reported no difference in osteolytic lesions between the HXLPE and control (even with differences in head penetration), but noted their followups were short and that more time may be required for differences to manifest [2,4,9,19,20,27].…”
Section: Discussionsupporting
confidence: 70%
“…Rajadhyaksha et al, also comparing Crossfire with a control group of N 2 Vac polyethylene, noted a difference in lysis similar to ours (0% versus 14.8%) [23]. Some studies reported no difference in osteolytic lesions between the HXLPE and control (even with differences in head penetration), but noted their followups were short and that more time may be required for differences to manifest [2,4,9,19,20,27].…”
Section: Discussionsupporting
confidence: 70%
“…Our data indicate contemporary THA provides improved hip function and stable implant fixation at short-to midterm followup. All bearing surface failures were the result of conventional polyethylene wear and/or osteolysis, which suggests future studies should investigate the performance of alternative bearing materials [25]. Cementless fixation combined with improved THA bearing materials may provide long-term survivorship even in the young patient population.…”
Section: Discussionmentioning
confidence: 99%
“…A radiograph taken between 12-18 months after surgery was used as a baseline for the measurement of steady-wear rate to account for bedding-in of the liner within the acetabular shell [50]. The resultant data was processed using the two measurements approach as described by Shia et al [46]. Volumetric wear is calculated from the magnitude of the wear vector on the two-dimensional projection on AP radiograph and the direction of the wear with respect to the cup face and the femoral head size [24, 36].…”
Section: Methodsmentioning
confidence: 99%